Biomarkers in Rare Demyelinating Disease of the Central Nervous System - Boziki, Marina (Int J Mol Sci, 2020)
Rare neurological diseases are a heterogeneous group corresponding approximately to 50% of all rare diseases. Neurologists are among the main specialists involved in their diagnostic investigation. At the moment, a consensus guideline on which neurologists may base clinical suspicion is not available. Moreover, neurologists need guidance with respect to screening investigations that may be performed. In this respect, biomarker research has emerged as a particularly active field due to its potential applications in clinical practice. With respect to autoimmune demyelinating diseases of the Central Nervous System (CNS), although these diseases occur in the frame of organ-specific autoimmunity, pathology of the disease itself is orchestrated among several anatomical and functional compartments. The differential diagnosis is broad and includes, but is not limited to, rare neurological diseases. Multiple Sclerosis (MS) needs to be differentially diagnosed from rare MS variants, Acute Disseminated Encephalomyelitis (ADEM), the range of Neuromyelitis Optica Spectrum Disorders (NMOSDs), Myelin Oligodendrocyte Glycoprotein (MOG) antibody disease and other systemic inflammatory diseases. Diagnostic biomarkers may facilitate timely diagnosis and proper disease management, preventing disease exacerbation due to misdiagnosis and false treatment. In this review, we will describe advances in biomarker research with respect to rare neuroinflammatory disease of the CNS.